Urban Loneliness in Surabaya: A Phenomenological Study of Hybrid Social Capital and Mental Health Vulnerability - Effendi, Masitah (The Sociology of Islam, 2025)
This study aims to understand urban loneliness in Surabaya and to explain how configurations of hybrid social capital combining offline and online relations shape urban residents' vulnerability to mental health problems. The research employs a qualitative approach, using interpretative phenomenological analysis, through in-depth interviews with a purposively selected number of informants based on age, length of residence, and level of engagement with digital media. The primary theoretical framework applied is Robert Putnam's social capital theory, particularly the distinction between bonding and bridging social capital in the context of urban life. The findings indicate that loneliness does not arise from a quantitative absence of social relations, but rather from the weakened quality of meaningful, stable, and emotionally supportive relationships. The dominance of broad yet shallow social networks strengthens bridging social capital while weakening bonding social capital, leaving individuals socially connected but with few reliable sources of emotional support. Such configurations of social capital render loneliness a structural condition of urban life that contributes to increased vulnerability to mental health disorders.